2017
DOI: 10.1007/s00394-017-1517-9
|View full text |Cite
|
Sign up to set email alerts
|

Consumption of extra virgin olive oil improves body composition and blood pressure in women with excess body fat: a randomized, double-blinded, placebo-controlled clinical trial

Abstract: EVOO consumption reduced body fat and improved blood pressure. Our results indicate that EVOO should be included into energy-restricted programs for obesity treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
48
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(51 citation statements)
references
References 62 publications
2
48
1
Order By: Relevance
“…Several studies confirmed the beneficial effects of polyphenols in olive oil on heart disease risk factors and oxidative damage [ 37 , 38 , 39 , 40 ]. In addition, EVOO has been widely studied for its favorable effects on plasma concentrations of low-density lipoprotein cholesterol (LDL-C) and total cholesterol [ 33 , 39 , 41 , 42 , 43 ], as well as on blood pressure [ 43 , 44 , 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies confirmed the beneficial effects of polyphenols in olive oil on heart disease risk factors and oxidative damage [ 37 , 38 , 39 , 40 ]. In addition, EVOO has been widely studied for its favorable effects on plasma concentrations of low-density lipoprotein cholesterol (LDL-C) and total cholesterol [ 33 , 39 , 41 , 42 , 43 ], as well as on blood pressure [ 43 , 44 , 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although the CVD influence of the MedDiet is mediated by the combination of different foods and healthy lifestyle habits, some specific polyphenol-rich dietary components might be more effective than others in modulating BP and conferring vasoprotection, particularly on a background of IR. EVOO with high polyphenols is probably the most important food from this point of view, being able to improve body composition and reduce BP in obese hypertensive women [198]. The anti-hypertensive actions of EVOO, and EVOO-related functional compounds, appear to be related to an increased endothelial synthesis of nitric oxide (NO), a potent vasodilator [198,199], which is disrupted in carriers of Glu298Asp polymorphism in the endothelial NO synthase (eNOS) gene [200] as well as under IR conditions [201], together with a decreased endothelial synthesis of the vasoconstrictor endothelin (ET-1) [199].…”
Section: Meddiet Evoo and Evoo-derived Polyphenols On Hypertensionmentioning
confidence: 99%
“…EVOO with high polyphenols is probably the most important food from this point of view, being able to improve body composition and reduce BP in obese hypertensive women [198]. The anti-hypertensive actions of EVOO, and EVOO-related functional compounds, appear to be related to an increased endothelial synthesis of nitric oxide (NO), a potent vasodilator [198,199], which is disrupted in carriers of Glu298Asp polymorphism in the endothelial NO synthase (eNOS) gene [200] as well as under IR conditions [201], together with a decreased endothelial synthesis of the vasoconstrictor endothelin (ET-1) [199]. The NO/ET-1 unbalance, which alters the vascular tone and drives hypertension, can be induced by increased plasma levels of FFAs and glucose, two well-known features of IR states [201].…”
Section: Meddiet Evoo and Evoo-derived Polyphenols On Hypertensionmentioning
confidence: 99%
“…So far, no mechanisms that connect the SUA level with the fatty acid profile of the diet have been found. However, some studies have shown that dietary intervention associated with a modification of the intake of fatty acids affects the SUA concentration (Galvão Cândido et al, 2018).…”
Section: Discussionmentioning
confidence: 99%